Incidence of self-concept on the academic performance of secondary education students (Encuentros, 2021)
This research sought to establish the relationship between the self-concept and the academic performance of students in the ninth, tenth and eleventh grades of the Bello Horizonte educational institution. For this investigation, a quantitative cross-sectional correlational study was carried out, a stratified non-probabilistic sampling was carried out and the AF-5 questionnaire assessing the Social, Academic / Professional, Emotional, Family dimensions was used to collect the information. and Physics and academic performance information was handled through information from the second source of EI's academic record Beautiful horizon. The results allowed to show that the academic self-concept presents distributions in the high deciles and emotional self-concept in the low deciles, which is reflected in the life cycle of the students. In conclusion, only a significant correlation was observed between physical self-concept and the subject of natural sciences. Keywords: self-concept, academic performance, physical self-concept, emotional self-concept, family self-concept.